Nasoalveolar Molding: Assessing the Burden of Care. Issue 2 (6th March 2021) - Wlodarczyk, Jordan R.; Wolfswinkel, Erik M.; Fahradyan, Artur; Rhee, Claire; Liu, Alice; Gibreel, Waleed; Magee, William; ,; Urata, Mark M.; Hammoudeh, Jeffrey A.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Over the last 3 years a shift at our institution has taken place in which patients who would have been offered nasoalveolar molding (NAM) as an adjunct to cleft lip repair (repair after 3 months) have instead undergone early cleft lip repair (ECLR) (2–5 weeks of life) without NAM. This study sought to examine the financial and social impact of the transition away from NAM to ECLR. The efficacy of NAM is limited by patient compliance to a rigorous treatment schedule requiring weekly visits for appliance adjustments. Nasoalveolar molding patients required an average of 11 dental visits, accounting for $2132 in indirect lost income per family. Average direct charges for NAM totaled $12, 290 for the hospital, physician, and appliance costs. Over the entire study period, the cumulative direct cost of NAM separate from the surgical repair of the lip was $970, 910. Following the introduction of ECLR as an alternative to NAM with standard lip repair, NAM usage decreased by 48% and unilateral cleft lip patients undergoing NAM decreased by 86%. Those diverted from NAM to ECLR resulted in a decreased healthcare cost burden of $368, 700 ($111, 727 per year). In addition to the time burden, the financial burden of NAM is significant. Early cleft lip repair without NAM is more cost effective. Nasoalveolar molding has significantly decreased utilization since the implementation of ECLR. We believe that ECLR, with increased experience, long-term data, and increased awareness, has the potential to decrease the burden of health care costs in the United States.